(untitled) (Research, Society and Development, 2021)
Objective: To analyze the evaluability of the Experiences and Internships Project in the Reality of the Unified Health System (VER-SUS). Methodology: Evaluability study, with a qualitative approach, carried out in the state of Piauí. Analysis of official VER-SUS documents was carried out, interviews with 32 actors involved in the execution of the project and construction of consensus on the results of the evaluability. The empirical material was subjected to thematic content analysis. Results: The objectives and goals of the VER-SUS Project were identified, as well as its operationalization in the state of Piauí, which subsidized the Logical Model systematization. This was submitted to the appreciation of the actors interviewed who participated in the execution of the project, establishing a consensus in relation to the assumptions, internal coherence and the problem to be solved by the project, considering the expected results and impacts. Conclusion: The results showed that VER-SUS is subject to evaluation, since the logical model allowed the identification of dimensions that constitute priority focuses of evaluation processes aimed at assessing their effectiveness, whose main problem is the formation of critical and sensitive professionals. needs of the population and the strengthening of the Unified Health System.